2007
DOI: 10.1186/1742-6413-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ObjectiveHyperchromatic crowded groups (HCG), a term first introduced into the cytology literature by DeMay in 1995, are commonly observed in Pap tests and may rarely be associated with serious but difficult to interpret lesions. In this study, we specifically defined HCG as dark crowded cell groups with more than 15 cells which can be identified at 10× screening magnification.MethodsWe evaluated consecutive liquid-based (Surepath) Pap tests from 601 women (age 17–74 years, mean age 29.4 yrs) and observed HCG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
(21 reference statements)
0
21
1
Order By: Relevance
“…Previous studies have shown that the vast majority of these HCGs are benign and include 3-dimensional endocervical cells, reactive endocervical cells, endometrial cells, tubal metaplasia, parabasal cells in atrophy, and inflammatory cells [1,18,19]. However, HCGs may also represent precancerous or malignant lesions and the difficulty in cytologic interpretation may cause a significant diagnostic pitfall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the vast majority of these HCGs are benign and include 3-dimensional endocervical cells, reactive endocervical cells, endometrial cells, tubal metaplasia, parabasal cells in atrophy, and inflammatory cells [1,18,19]. However, HCGs may also represent precancerous or malignant lesions and the difficulty in cytologic interpretation may cause a significant diagnostic pitfall.…”
Section: Discussionmentioning
confidence: 99%
“…HCGs are frequently encountered in liquid-based cervical cytology and can be seen in as many as 79% of Pap specimens [1]. Previous studies have shown that the vast majority of these HCGs are benign and include 3-dimensional endocervical cells, reactive endocervical cells, endometrial cells, tubal metaplasia, parabasal cells in atrophy, and inflammatory cells [1,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] The glandular spectrum of HCG from MGH may also display mild cytologic atypia with nuclear enlargement and hyperchromasia. [ 2 ] The cells may have multiple nucleoli, mitotic figures, and apoptotic bodies (normoblast- like apoptosis in squamous metaplastic cells). [ 1 , 2 ] AIS (option B), which is typically asymptomatic, demonstrates a different cytologic spectrum.…”
Section: Explanationmentioning
confidence: 99%
“…[ 2 ] The cells may have multiple nucleoli, mitotic figures, and apoptotic bodies (normoblast- like apoptosis in squamous metaplastic cells). [ 1 , 2 ] AIS (option B), which is typically asymptomatic, demonstrates a different cytologic spectrum. AIS displays crowded sheets of stratified and enlarged cigar-shaped glandular cells with hyperchromatic nuclei with coarse chromatin, relatively inconspicuous nucleoli, mitoses, particularly in an apical location, and apoptotic bodies.…”
Section: Explanationmentioning
confidence: 99%